PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI: PERAWAT RS TELOGOREJO SEMARANG) - Hernita Eka Talashina; Ngatno Ngatno (Universitas Diponegoro, 2020)
Quality human resources were one of the key factors for the success of a business. Based on the data obtained, employee performance at telogorejo hospital in semarang shows fluctuating figures that tended to decrease in 2018. Through the results of preliminary studies, it could be seen that there were indications of a decrease in employee job satisfaction caused by compensation and work motivation. Thus, decreased job satisfaction was thought to caused a decrease in employee performance. This typed of researched was explanatory researched that explains between variables through hypothesis testing. Sampling using a convenience sampling technique as many as 177 respondents who were nurses telogorejo hospital semarang.Data collection techniques using questionnaires and literature studied. This researched uses quantitative analysis with validity, reliability, correlation coefficient, determination coefficient, regression analysis, t-test with the help of ibm spss version 16. 0 and sobel analysis to test the effect of intervening variables. Based on the results of the studied indicate that compensation and work motivation partially had a significant effect on job satisfaction, job satisfaction had a significant effect on performance, job satisfaction could mediate the effect of compensation on performance as a partial intervening variable and could mediate the effect of work motivation on performance as a partial intervening variable. The advice given to improved employee performance was to considered nurses' input on the policy of base salary that must be adjusted to the workability of nurses, as well as to determine the number of individual achievement incentives. To increase work motivation by applying a sensed of openness between nurses and company leaders as well as establishing fraternal relations between each nurse, and regular training needs to be held to improved the ability of nurses in providing health services so that it will affect nurse job satisfaction which ultimately affects employee performance.